Are Filipinos Really Hate Duterte’s Leadership? - Dano, Givheart (Papanda Publishier, 2024)
This study aims to determine whether Filipinos genuinely hold negative feelings towards President Duterte’s leadership. It analyzes public opinions through existing surveys, media discussions, and socio-political group actions. Using a descriptive research approach, the study seeks to understand the diverse perspectives on Duterte’s leadership in the Philippines. It explores the reasons behind both support and criticism, taking into account factors such as economic policies, leadership style, and responses to significant events during his presidency. By uncovering the various influences on people’s opinions in a changing political and social landscape, the research aims to provide valuable insights into the complex sentiments surrounding Duterte’s leadership. Despite facing widespread criticism for his authoritarian leadership style, war on drugs, and attacks on the media, President Rodrigo Duterte maintained high levels of public support throughout his presidency. The study concludes that Duterte’s leadership has both strengths and weaknesses, with high approval ratings attributed to his perceived strength, populist messaging, and effective communication. While not universally trusted, Duterte’s ability to connect with a significant portion of the population suggests a willingness among Filipinos to support leaders who promise to address their concerns, even in the face of authoritarian measures. Overall, this research contributes valuable insights into the intricate tapestry of sentiments surrounding Duterte’s leadership, shedding light on the diverse perspectives that define the Filipino public’s stance on their president.